Curcumin liposomes interfere with quorum sensing system of Aeromonas sobria and in silico analysis - Ting Ding (Nature Portfolio, 2017)
Abstract Aeromonas sobria is opportunistic pathogen frequently found in environment and food. Interfering with its quorum sensing (QS) system could be a promising way to alleviate its virulence. In this study, curcumin liposomes were prepared and their characteristics like particle size, zeta potential, PDI (Polymey Disperse Index), encapsulation efficiency and loading capacity were measured. The quorum sensing inhibitory effect of curcumin liposomes under sub-MIC (Minimum Inhibitory Concentration) on siderophore production, swimming and swarming motility, extracellular proteases, biofilm formation and AHLs (N-acylhomoserine lactones) production of A. sobria were also determined. The results showed that, the curcumin liposomes with high encapsulation capacity (84.51 ± 0.58%) were stable and homogeneous. QS-regulated phenotypes of the pathogen were significantly inhibited by curcumin liposomes. The in silico analysis revealed that the QS system of A. sobria may be inhibited by released curcumin from curcumin liposomes through interacting with the built LuxI type protein and blocking the production of AHLs.